2012
DOI: 10.1128/jvi.00121-12
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Analysis of the Complex between the Tetrameric Export Adapter Protein Rec of HERV-K/HML-2 and the Responsive RNA Element RcRE pck30

Abstract: The RNA export adaptor protein Rec, encoded for by the human endogenous retrovirus HERV-K/HML-2 elements, binds to the Rec responsive element (RcRE) located in the 3′ untranslated region of HERV-K/HML-2 transcripts. Binding allows the nucleocytoplasmic export of unspliced viral RNA, thereby overcoming host restriction. Chemical probing of the secondary structure of the RcRE corroborated the theory that the RcRE forms a complex folded structure with seven stem-loop regions. Laser-induced liquid beam ion desorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
(72 reference statements)
0
9
0
Order By: Relevance
“…The NLS also recognizes the Rec-responsive element (RcRE) within the viral RNAs (vRNAs). Rec forms tetramers and, presumably, three tetramers bind to purine-rich stretches within the RcRE (Langner et al 2012). To achieve its nucleocytoplasmic function Rec interacts with Staufen-1, which is also involved in utilization of the cargo RNA for efficient transport and particle encapsidation (Hanke, Hohn, et al 2013).…”
Section: Hml-2 Structure: Genes Transcripts and Proteinsmentioning
confidence: 99%
“…The NLS also recognizes the Rec-responsive element (RcRE) within the viral RNAs (vRNAs). Rec forms tetramers and, presumably, three tetramers bind to purine-rich stretches within the RcRE (Langner et al 2012). To achieve its nucleocytoplasmic function Rec interacts with Staufen-1, which is also involved in utilization of the cargo RNA for efficient transport and particle encapsidation (Hanke, Hohn, et al 2013).…”
Section: Hml-2 Structure: Genes Transcripts and Proteinsmentioning
confidence: 99%
“…The mechanism(s) responsible for the difference in relative HIV-1 Rev or HERV-K Rec activity when paired with different HERV-K RcREs was not examined in this study. It has been previously proposed that different stem-loops in the prototypical HERV-K RcRE sequence may be involved in binding to Rev and Rec (31,60,61). For HIV-1 Rev, it has been suggested that there may be two discrete binding sites that lie within stem-loop 2 and 6, while for HERV-K Rec, binding between the protein and RNA may be much more complex, involving folding and three-dimensional structure rather than discrete binding sites within the HERV-K RcRE.…”
Section: Discussionmentioning
confidence: 99%
“…Rec is a small RNA-binding protein considered to be a functional homolog of the HIV Rev accessory protein [13]. Rec contains a nuclear localization signal (NLS), which in addition to facilitating nuclear transport of the Rec protein, recognizes the Recresponsive element (RcRE) within the viral RNAs [14,18]. Binding of Rec to RcRE stabilizes incompletely spliced/unspliced viral transcripts and enhance their nuclear export [8,19,20] via the CRM1 export pathway [12,13,21].…”
Section: Introductionmentioning
confidence: 99%